Predictors of Hearing Protection Behavior Among Power Plant Workers - Youngmi Kim, PhD, RN; Ihnsook Jeong, PhD, RN; Oi-Saeng Hong, PhD, RN (Elsevier, 2010)
This study aimed to identify factors affecting the use of the hearing protection devices (HPDs) among workers exposed to noise using the Pender Health Promotion Model. Methods: The 222 subjects came from thermal power plants with similar noise levels, which are between 80 dB and 90 dB in South Korea. Data were collected with self-administered questionnaires designed to measure concepts from the Health Promotion Model. Results: Mean percent times of using the HPDs at their most recent job site were 50.9%, and 20.3% had never the HPDs. The predictors of HPD use were social modeling (OR = 1.380), perceived benefits (OR = 1.150), and working at noisy worksites (OR = 4.925) when the outcome was based on the "non-use" versus "used at least once". However, the predictors of HPD use were social modeling (OR = 1.795) and perceived benefits (OR = 1.139) based on the "less than half-of-the-time-use" versus "more than half-of-the-time-use". Conclusion: Social modeling and perceived benefits of using the HPDs are important for workers to keep minimal or certain level of using the HPDs.